2018
DOI: 10.1093/annonc/mdy426.002
|View full text |Cite
|
Sign up to set email alerts
|

HER2 positive rates in invasive lobular breast carcinoma: A study amongst 1,095 consecutive Asian patients

Abstract: Background: TP53 mutation is the most common mutation in breast cancer, and it is considered a target marker of triple negative breast cancer (TNBC). The purpose of this study was to evaluate the prognosis of TNBC using only clinical information. The p53 status detected immunohistochemically was evaluated as a prognostic and predictive factor. Methods: Among KBCSR-registered patients, triple-negative breast cancer patients diagnosed between 2000 and 2015 were included. This included patients who were aged 20 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our results do agree with others in that most cases of ILC with HER2 overexpression represented the pleomorphic variant (26). Kee et al reported a higher prevalence of HER2positive classic type ILC (10.8%) compared to the previous ILC case series (1-6%) (27). In the study of Prati et al, only three cases of 31 (9.7%) ILCs out of 200 breast cancer cases had positive HER2 results by FISH (10).…”
Section: Discussionsupporting
confidence: 91%
“…Our results do agree with others in that most cases of ILC with HER2 overexpression represented the pleomorphic variant (26). Kee et al reported a higher prevalence of HER2positive classic type ILC (10.8%) compared to the previous ILC case series (1-6%) (27). In the study of Prati et al, only three cases of 31 (9.7%) ILCs out of 200 breast cancer cases had positive HER2 results by FISH (10).…”
Section: Discussionsupporting
confidence: 91%